Ferroportin depletes iron needed for cell cycle progression in head and neck squamous cell carcinoma - Belvin, Benjamin Ross; Lewis, Janina P. (Frontiers in Oncology, 2023)
Introduction Ferroportin (FPN), the only identified eukaryotic iron efflux channel, plays an important role in iron homeostasis and is downregulated in many cancers. To determine if iron related pathways are important for Head and Neck Squamous Cell Carcinoma (HNSCC) progression and proliferation, we utilize a model of FPN over-expression to simulate iron depletion and probe associated molecular pathways. Methods The state of iron related proteins and ferroptosis sensitivity was assessed in a panel of metastatic HNSCC cell lines. Stable, inducible expression of FPN was confirmed in the metastatic HNSCC lines HN12 and JHU-022 as well as the non-transformed normal oral keratinocyte (NOK) cell line and the effect of FPN mediated iron depletion was assessed in these cell lines. Results HNSCC cells are sensitive to iron chelation and ferroptosis, but the non-transformed NOK cell line is not. We found that FPN expression inhibits HNSCC cell proliferation and colony formation but NOK cells are unaffected. Inhibition of cell proliferation is rescued by the addition of hepcidin. Decreases in proliferation are due to the disruption of iron homeostasis via loss of labile iron caused by elevated FPN levels. This in turn protects HNSCC cells from ferroptotic cell death. Expression of FPN induces DNA damage, activates p21, and reduces levels of cyclin proteins thereby inhibiting cell cycle progression of HNSCC cells, arresting cells in the S-phase. Induction of FPN severely inhibits Edu incorporation and increased β-galactosidase activity, indicating cells have entered senescence. Finally, in an oral orthotopic mouse xenograft model, FPN induction yields a significant decrease in tumor growth. Conclusions Our results indicate that iron plays a role in HNSCC cell proliferation and growth and is important for cell cycle progression. Iron based interventional strategies such as ferroptosis or iron chelation may have potential therapeutic benefits in advanced HNSCC.